Pomiar wartości godziwej - standard FASB i tworzenie nowego MSSF - Hasik, Wojciech (Fair Value Measurement - the FASB Standard and the Creation of New IFRS, 2007)
Fair value is one of the most controversial issues in contemporary accounting, both for practitioners and academics. The goal of this paper is to analyze the most important regulations of SFAS no. 157 Fair Value Measurements, which has been issued in September 2006 by FASB. This standard was accepted by IASB as the platform to develop the new IFRS on fair value. Therefore its regulations will be most likely implemented in the future praxis of accounting of all European public listed companies. It will determine the practice of fair value in Poland as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 204-211